STRATEGI PEMASARAN MOBIL SEKEN DI CV AUTO CLASS PERSADA PADANG - Bernadetta Sakoikoi; Donna Ikranova Febrina; Mellati Mandasari (Jurnal Public Administration, Business and Rural Development Planning, 2022)
The aims of this research are: 1) To find out the marketing strategy in CV Auto Class Persada Padang. This research was conducted using descriptive qualitative research methods. Resources obtained from CV Auto Class Persada Padang. Methods of data collection using interviews, observation, document analysis. The results of the research that the authors get are 1) The marketing strategy at CV Auto Class Persada Padang is a) the mindset that is applied to improve the quality of coordination in the marketing team. b) searching for data through observations and interviews conducted to the intended target market, is useful for knowing tastes and purchasing power. c) Determining market positioning (Marketing Positioning) many things can be done by companies such as providing competitive prices and many more efforts that can be made to win the hearts of customers. d) This marketing mix has a very important role for the success of a company's business in general and in the field of marketing in particular. e) Budgeting is an important part of planning a realistic and controllable marketing strategy. From the conclusions above, it is suggested the following: 1) To maintain the condition of CV in order to remain in a favorable position, it is better for CV Auto Class Persada Padang to support marketing strategy by carrying out stages including: improving the quality of coordination within the marketing team, utilizing technological advances to be closer to the customer.